Limits of body composition assessment by bioelectrical impedance analysis (BIA) - Wasyluk, Weronika; Wasyluk, Martyna; Zwolak, Agnieszka; Łuczyk, Robert Jan (Journal of Education, Health and Sport, 2019)
Bioelectrical impedance analysis (BIA) is a safe, non-invasive and repeatable method of body composition assessment, based on diversified electrical conduction through the aqueous and fat compartment of the body. The popularity and availability of the BIA study has increased in recent years. The aim of the work is to discuss its limitations, which can be divided into factors affecting the measurement of parameters and contraindications for measurements. The first group includes body structure, obesity and malnutrition, body temperature, intake of fluids and foods, changes in hydration and water and electrolyte balance, physical activity, long-term staying in a supine position, examination procedure and method of placing measuring electrodes. Contraindications include implanted cardiac devices (cardiac pacemaker, implantable cardioverter-defibrillator, resynchronization therapy), metal implants and pregnancy. There is no unambiguous confirmation of the validity of the mentioned contraindications in literature. Knowing the limitations of BIA is important because parts of potential errors can be avoided by properly preparing for the examination and following appropriate procedures during the measurements.